Internalization of Multicultural Values in Learning the Art of Recitation to Form the Attitude of Social Tolerance of Students at the Al-Qur'an Education Park Baiturrahman Gading Kasri Malang - Muhammad Yusuf Asro; Fita Mustafida; Imam Safi'i (Green Publisher Indonesia, 2026)
In many non-formal Islamic institutions, learning still emphasizes cognitive and technical skills, while affective aspects such as tolerance are often underdeveloped. Therefore, this research aims to analyze the internalization of multicultural values in learning the art of Qur’anic recitation and its role in shaping students’ social tolerance at TPQ Baiturrahman Gading Kasri Malang. This study employs a descriptive qualitative approach with a narrative design. Data were collected through observations, in-depth interviews, and documentation involving teachers, students, and the head of the institution. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that multicultural values internalized in recitation learning include tolerance, justice, and cooperation. These values are integrated through interactive learning activities such as group practice, peer support, and participation in internal and external Musabaqah Tilawatil Qur’an (MTQ). The internalization process occurs through value transformation, value transaction, and transinternalization, supported by teacher modeling and a conducive learning environment. As a result, students demonstrate improved social attitudes, including empathy, mutual respect, cooperation, and confidence in social interactions. In conclusion, learning the art of Qur’anic recitation is not only effective in improving technical reading skills but also plays a significant role in fostering multicultural values and strengthening students’ social tolerance. This approach contributes to the development of harmonious social behavior in diverse educational settings.